Photoassociative ionization in cold rubidium - Trachy, Marc Lawrence (Kansas State University, 2008)
Many people in the science community are interested in the prospect of cold molecules for such applications as quantum computing and molecular Bose-Einstein condensates. Current methods of production fall short of the requirements for such projects. Photo association is a promising technique for forming cold molecules, but is currently facing significant obstacles. By understanding the photo association process and utilizing higher excited states, it is hoped that cold molecules can be formed from more easily produced cold atoms. Photo associative Ionization (PAI) is presented as a means to study excited state molecular dynamics at large internuclear separation, including photo association. This thesis presents a number of techniques for studying PAI in cold rubidium and a number of results obtained with the techniques. Excitation pathways for the process are explored in both narrow linewidth (MHz) and ultrafast (fs), large bandwidth (20 nm) domains.
Keywords: Photoassociation; Photoassociative ionization; Physics, Atomic (0748); Physics, Molecular (0609); Physics, Optics (0752)